2016
DOI: 10.1186/s11556-016-0163-1
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Advanced Glycation End product (AGE) accumulation to the decline in motor function

Abstract: Diminishing motor function is commonly observed in the elderly population and is associated with a wide range of adverse health consequences. Advanced Glycation End products (AGE’s) may contribute to age-related decline in the function of cells and tissues in normal ageing. Although the negative effect of AGE’s on the biomechanical properties of musculoskeletal tissues and the central nervous system have been previously described, the evidence regarding the effect on motor function is fragmented, and a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
1
25
0
1
Order By: Relevance
“…Skin AF, representing the accumulation of AGEs, was inversely associated with SMI, grip strength and knee extension strength in an adjusted multivariate logistic regression model in the present study. As reported previously, reduced muscle mass, regarded as the primary phenotype of sarcopenia, is associated with accumulated AGEs in humans as they age. Oxidative stress and inflammatory cytokines are increased by AGEs.…”
Section: Discussionsupporting
confidence: 60%
“…Skin AF, representing the accumulation of AGEs, was inversely associated with SMI, grip strength and knee extension strength in an adjusted multivariate logistic regression model in the present study. As reported previously, reduced muscle mass, regarded as the primary phenotype of sarcopenia, is associated with accumulated AGEs in humans as they age. Oxidative stress and inflammatory cytokines are increased by AGEs.…”
Section: Discussionsupporting
confidence: 60%
“…The expression of AGER showed a significant increase in the sperm from D ‐gal‐induced aged rats compared with the control rats. It has been reported that the increased level of AGE is responsible for accelerated aging in D ‐gal‐induced aging model ( Drenth et al, ) . There are now evidence that that D ‐gal treatment also causing the reproductive aging, characterized by decreased sperm count, testis weight, serum testosterone, and LH levels (Ahangarpour et al, ; Liao et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Гликозилированные молекулы возбуждают сигналь-ные пути, ассоциированные с мембранными AGE-связывающими рецепторами (AGE-R1, AGE-R2, R3-AGE и RAGE). Активация AGE-связывающих рецепторов индуцирует генерацию активированных кислородсодержащих метаболитов, которые иници-ируют возбуждение провоспалительного сигналь-ного каскада, обусловливая продукцию нескольких цитокинов и факторов роста, вызывающих инду-цированное гипергликемией повреждение клеток и воспаление [10]. Гликозилированные продукты также способствуют накоплению внутриклеточной воды и развитию отека тканей.…”
Section: ключевые слова: хейропатия; сахарный диабет 1-го типа; детиunclassified